Change and Predictors of Change in Social Skills of Nursing Home Residents With Dementia. (February 2014) - Chappell, Neena L.; Kadlec, Helena; Reid, Colin
Background: Social skills are of primary importance for those with dementia and their care providers, yet we know little about the extent to which basic social skills can be maintained over time and the predictors of change. Methods: A total of 18 nursing homes with 149 newly admitted residents with moderate to severe dementia, 195 direct care staff, and 135 family members, in British Columbia, Canada, contributed data on change in social skills from admission to 6 months and 1 year later. Results: Three-quarters of residents maintained or improved their basic social skills during both the time periods. Decline was explained primarily by cognitive status at the time of admission, notably present orientation. However, staff-to-resident communication becomes more important over time. Conclusions: Social skills appear to present an opportunity to maintain interaction with these residents. The findings also suggest that a focus on the present orientation before and following admission and on staff-to-resident communication may be beneficial.